2014
DOI: 10.1016/j.juro.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Early and Late Complications after Oral Mucosal Graft Harvesting: Multivariable Analysis from a Cohort of 553 Consecutive Patients

Abstract: Harvesting the oral mucosa ovoid graft from a single cheek with closure of the wound is a safe procedure with high rates of patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 16 publications
2
48
0
2
Order By: Relevance
“…The oral mucosa graft was harvested from the cheek according to our standard technique used on more than 553 patients. [7] The graft was tailored as per individual case. The patient was placed in supine position.…”
Section: Methodsmentioning
confidence: 99%
“…The oral mucosa graft was harvested from the cheek according to our standard technique used on more than 553 patients. [7] The graft was tailored as per individual case. The patient was placed in supine position.…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29] A meta-analysis of a total of 17 series with 1234 patients similarly confirmed greater than 93% success of EPA in the management of bulbar urethral stricture disease. 28 Complications following EPA performance are usually minimal and transient.…”
Section: Anastomotic Techniques Excision With Primary Anastomosis (Epmentioning
confidence: 89%
“…3,33 The most appropriate candidates for vessel-sparing EPA appear to be those with short, proximal bulbar strictures. 29 Performance of vessel-sparing EPA is technically challenging and a significant learning curve is likely required.…”
Section: Vessel/spongiosum-sparing Epa Urethroplastymentioning
confidence: 99%
“…In a retrospective study of oral mucosal graft harvesting, Barbagli et al . found that bilateral graft harvesting in long strictures was a significant predictor of patient dissatisfaction . BEES‐HAUS, an endoscopic tissue engineering‐based cell therapy, has tremendous potential even in recurrent and long strictures.…”
Section: Discussionmentioning
confidence: 99%